Development of a 13 L Portable Sandblasting System: Design, Fabrication, and Surface Roughness Analysis on Aluminum - Rofi Romadhon, Saeful; Sugiarto, Tris; Ismail, Adhan; Priwintoko, Baharudin (Creative Research in Engineering (CERIE), 2026)
Surface preparation plays a vital role in improving coating adhesion and corrosion resistance of metals. Conventional techniques such as sanding or chemical etching are often inefficient, hazardous, or unsuitable for small-scale workshops. Sandblasting provides a more effective solution; however, existing systems are typically bulky and costly. This study aimed to design and evaluate a portable dry sandblasting prototype with a 13 L pressure vessel and maximum operating pressure of 8 bar, developed using the Systematic Engineering Design Method. Aluminum specimens were blasted using silica sand (80 mesh) under varying air pressures (4, 5, and 6 bar) and nozzle distances (10, 15, and 20 cm), with spraying time fixed at 20 seconds. Surface roughness was measured with a Surfcorder Fowler SE1700 (JIS B 0601 standard), and macroscopic observations were performed to assess surface morphology. Results indicated that roughness increased with air pressure and decreased with nozzle distance. The untreated specimen had an Ra of 0.69 µm, rising to 7.92 µm at 6 bar and 10 cm. Several conditions, particularly ≥5 bar and ≤15 cm, produced Ra values above 5 µm, sufficient to improve coating adhesion. The study confirms the prototype’s effectiveness and novelty in combining design and validation, offering a compact, low-cost solution for SMEs and automotive workshops.